2017
DOI: 10.37856/bja.v92i1.3269
|View full text |Cite
|
Sign up to set email alerts
|

Super Sweet Corn Breeding by Backcross: A New Choice for the Brazilian Market

Abstract: The sweet corn market has been expanding in recent years and the trend is to maintain this growth, targeting mainly the export market. The goal was to evaluate the agronomic performance per se and hybrid backcrosses of four sweet corn populations and to estimate genetic parameters inherent in these populations, in order to achieve promising lines to obtain hybrids. The following genotypes were used for a test: the donor population sh gene, two recurring populations interpopulation hybrids of common maize, four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 4 publications
1
7
0
1
Order By: Relevance
“…This observed yield potential reflects the great prospects that abound for sweet corn production in Nigeria. The findings of this study confirmed previous reports (Cartea et al, 1996;Malvar et al, 1997Malvar et al, , 2001Tracy, 2001;Butrón et al, 2008;Santos et al, 2014;Entringer et al, 2017) on the potential of tropical field maize genotypes in the improvement of sweet corn.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This observed yield potential reflects the great prospects that abound for sweet corn production in Nigeria. The findings of this study confirmed previous reports (Cartea et al, 1996;Malvar et al, 1997Malvar et al, , 2001Tracy, 2001;Butrón et al, 2008;Santos et al, 2014;Entringer et al, 2017) on the potential of tropical field maize genotypes in the improvement of sweet corn.…”
Section: Discussionsupporting
confidence: 92%
“…This strategy will lead to improvement in the yield of the super-sweet corn varieties, broaden the narrow genetic base characteristic of sh2 (Tracy, 2001;Teixeira et al, 2013), and facilitate the development of sh2 inbred lines and hybrids. According to Entringer et al (2017), the backcross method of breeding is efficient for obtaining super-sweet corn populations with good agronomic performance. Previous studies Cartea et al (1996), Malvar et al (1997Malvar et al ( , 2001, Tracy (2001), Butrón et al (2008) and Entringer et al (2017) reported the use of field corn to improve the agronomic performance of sweet corn.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One way to improve the performance of this tropicalised population and broaden it genetic base is by crossing the sh2 maize with the more adapted field maize germplasm, which could be sources of favourable alleles for enhanced agronomic performance, as well as, increased disease and pest resistance. Previous studies (Tracy, 2001;Cartea et al, 1996;Malvar et al, 1997Malvar et al, , 2001Butrón et al, 2008;Entringer et al, 2017) have shown the utility of field corn in the improvement of agronomic performance of sweet corn. These studies have also indicated that field maize genotypes could differ in their ability to improve the agronomic performance and quality of sweet corn.…”
Section: Introductionmentioning
confidence: 98%
“…In both environments, the Cimmyt and Piranão populations reported lower plant height values. This can be attributed to genotypes having carriers of the brachytic gene, which gives a smaller size to the plants [19].…”
Section: Resultsmentioning
confidence: 99%